Compositional analysis of polymers : an engineering approach - Kochnev, Aleksandr M.; Stoyanov, Oleg V.; Zaikov, G. E. (Gennadiĭ Efremovich), 1935-; Akhmetkhanov, Renat M. (Apple Academic Press, 2016)
"Technical and technological development demands the creation of new materials that are stronger, more reliable, and more durable, i.e. materials with new properties. This new book covers a broad range of polymeric materials and technology and provides researchers in polymer science and technology with new research on the functional materials production chain. Chapters in this new volume highlight recent developments in advanced polymeric materials from macro- to nano-length scales. Composites are becoming more and more important as they can help to improve our quality of life. This volume presents the latest developments and trends in advanced polymer materials and structures. It discusses the developments of advanced polymers and respective tools to characterize and predict the material properties and behavior. This book has an important role in advancing polymer materials in macro and nanoscale. Its aim is to provide original, theoretical, and important experimental results that use non-routine methodologies. It also includes chapters on novel applications of more familiar experimental techniques and analyses of composite problems that indicate the need for new experimental approaches."--